Nichtgehfähige Patienten mit Duchenne-Muskeldystrophie - Flotats Bastardas, Marina; Ziegler, Andreas (Der Nervenarzt, 2019)
BackgroundDuchenne muscular dystrophy (DMD) is a severe X‑linked recessive neuromuscular disorder. In children without corticosteroid therapy, progressive muscular weakness is associated with loss of ambulation on average by the age of 9.5 years.Objective, material and methodsOn the basis of current guidelines, a group of experts in this field defined a number of clinical parameters and examinations that should be performed on a regular basis to assess changes over time in non-ambulant patients.Results and conclusionTo assess function of the upper extremities the Brooke upper extremity functional rating scale or the performance of upper limb test should be used. For assessment of pulmonary function measurement of forced vital capacity (FVC) is recommended. The extent of cardiac involvement can best be evaluated using cardiac magnetic resonance imaging (MRI), measurement of the ejection fraction (EF) and the left ventricular shortening fraction (LVSF) by echocardiography. The pediatric quality of life inventory should be used for assessment of quality of life. In addition, the body mass index (BMI), the number of infections and need for in-hospital treatment as well as early detection of orthopedic problems, most importantly the development of scoliosis should be monitored. After transition from pediatric to adult care DMD patients should be primarily cared for by adult neurologists and specialists in pulmonary and cardiac medicine.
Gesehen am 09.12.2019